Time out: National perspectives on sport and the Covid-19 lockdown (Common Ground Research Networks, 2021)
In the edited collection Time Out: National Perspectives on Sport and the Covid-19 Lockdown, practitioners and international scholars explore the impact of the global Covid-19 health pandemic on sport from various local and national perspectives. It is part of a two-volume Covid-19 and Sport series that tackles the effects of the global lockdown on sport during March and April 2020, when restrictions were at their most severe and the human toll at its peak in many countries. The chapters provide a comprehensive overview of the immediate consequences of the Covid-19 lockdown on local and national sport. This book presents a variety of interdisciplinary perspectives in a total of twenty-two individual chapters, organized around four main themes. In the first two sections, the authors address the response by professional sports within national contexts. In section three, the authors explore the effects and responses of the Covid-19 lockdown on leisure and amateur sports. The final section assesses the effect of the pandemic on national policies and media.